The Difference Practice of Condom Usage to Direct and Indirect Woman Sex Worker in Preventing HIV at Sidoarjo - Elok Puspita Sari; Arief Hargono (Jurnal Berkala Epidemiologi, 2015)
“Direct”Woman Sexual Workers (WPS-L) are women who openly peddle sex both on the streets or in localization while “Indirect” Woman Sexual Workers (WPS-TL) are a woman who peddles sex in disguise at certain occupations or have other main occupations and indirectly peddling sex such as massage, bar/karaoke waitress. The purpose of this study was to determine the differences in the use of WPS-L and WPS-TL condoms in the prevention of Human Immunodeficiency Virus (HIV) in Sidoarjo. This research is an observational descriptive study. The population consists of an estimated WPS-TL population of 20 people and an estimated WPS-L population of 233 people. Size determines of the sample for hypothesis testing using the Lemeshow formula 1: 2 ratio obtained WPS-TL samples of 20 people with total sampling techniques and WPS-L samples of 42 people with a simple random sampling technique. The variables studied were the characteristics and actions of the two sample groups. The results showed that the percentage of respondents with good condom use was found more in the WPS-L group (73.8%) than in the WPS-TL group (30%). The conclusion of this study is that there are differences in the use of WPS-L and WPS-TL condoms in HIV prevention in Sidoarjo. Suggestions for further researchers can expand the research sample, add other variables, and develop different research methodologies such as quantitative and experimental. For further research can expand the research sample, add other variables and develop research methodologies.